0–39%: The beginning of an infrastructure of failure in academia. (May 2020) - Turner, Jennifer
Abstract: This intervention draws upon Horton's (2008) recognition that failure is a ubiquitous component of academic life. However, it critiques his contention that this failure is 'unseen', particularly in the discipline of geography. Harrowell et al (2017), recognise failure as a powerful resource in spirit of the emancipation of academics who do encounter considerable 'failure' in their teaching and research work, as well as their academic careers more widely. Taking lead from Harrowell et al., this intervention extends this understanding of the power of failure, instead considering the structure of academia as intertwined with, and critically anchored to, a system of failure that starts at undergraduate level. Seemingly obfuscated from academic discussions, this failure – threat or otherwise reality – begins almost as soon as an undergraduate student registers for their degree and persists as a consequential, yet quotidian element of University work and study. This intervention draws attention to examples from undergraduate grading schemes/criteria to explore the visibility of infrastructures of failure to argue that, far from being an 'unseen' component of our academic workings, failure is very much a present, consistent and fundamental constituent of academic life that must be negotiated in order to succeed. Highlights: Academia is critically anchored to a system of failure that starts at undergraduate level. The visibility of failure can be highlighted in grading processes and marking criteria. This infrastructure of failure must be negotiated in order to succeed. This involves positively harnessing aspects of failure and/or redeveloping critique in academia.